Drastic Change in Photoluminescence Properties of Graphene Quantum Dots by Chromatographic Separation. Issue 10 (1st July 2014) - Fuyuno, Naoto; Kozawa, Daichi; Miyauchi, Yuhei; Mouri, Shinichiro; Kitaura, Ryo; Shinohara, Hisanori; Yasuda, Toku; Komatsu, Naoki; Matsuda, Kazunari
<x xml:space="preserve">Abstract</x> Graphene quantum dots (GQDs) have attracted a great deal of interest from the viewpoints of both fundamental studies and applications. Photoluminescence (PL) is one of the intriguing properties of GQDs, however, the mechanism of the PL in GQDs is not fully understood. In the present study, a drastic change in the PL from UV to red light region is reported among GQDs separated by size‐exclusion high performance liquid chromatography. It is confirmed by transmission electron microscopy images that the GQDs are separated by the difference in their overall sizes. Two‐dimensional PL excitation spectra of the chromatographically separated GQDs show four distinct emission peaks at ∼330, ∼440, ∼520, and ∼600 nm. The dominant luminescence features of the separated GQDs show discrete changes depending on the overall size of GQDs, indicating that the PL variation occurs because of differences in density, shape, and size of sp2 fragments available in the GQDs.